Yoga Arjuna Dalam Teks Kakawin Arjuna Wiwāha - Adi Brahman, I Made (Jurnal Penelitian Agama Hindu, 2024)
Yoga is a teaching that emerged and flows in line with Vedic civilization and continues to develop in line with the times. Patanjalis Yoga Sutra is ancient literature that can be used as a reference in understanding yoga. Yoga in its development in the Nusantara is widely described in several lontar texts which are classified as tattwa such as: Bhuana Kosa, Wrhaspati Tattwa, Tattwajnāna and Ganapati Tattwa. Kakawin Arjuna Wiwāha by Mpu Kanwa is a text which describes the yoga teachings practiced by Arjuna which is interesting and important to study. The aim of this research is to explore the process of Arjunas yoga in the Kakawin Arjuna Wiwāha text with the hope that it can provide new insights and can be used as a guide for yoga practitioners. This research includes qualitative research with the primary data source being the Kakawin Arjuna Wiwāha manuscript translated by I Wayan Djapa which was published by the Indonesian Hindu University Postgraduate Program in 2013. The data collection method was through library research and document study, and then the data was analyzed using the hermeneutic method. Research has found that yoga is an effort to control the senses and mind to know and realize God within oneself as the Atman. Yoga is done with the concept of amutȇr tutur pinahayu which is turning consciousness from body consciousness to Atman. Wiku Witaraga is the title for Arjuna who was able to control his sensual desires. Samadhi is the culmination of the practice of yoga where the Yogiswara gains a spiritual experience of his unity with God.